Digital Transformation of Road Safety Systems: A Mediating Model for Transportation Safety Pillars in Indonesia - Susanto EA Susanto EA; Sofilda E Sofilda E; Kunawangsih T Kunawangsih T; Ledoh DB Ledoh DB (MASI Mandiri Edukasi, 2026)
Road transportation safety remains a major public policy challenge in Indonesia, characterized by high accident rates and substantial socio-economic impacts. The government has introduced the National General Plan for Traffic and Road Transportation Safety 2021–2040, structured around five key safety pillars. However, policy implementation continues to face challenges, including institutional fragmentation, weak cross-sectoral coordination, limited data integration, and the suboptimal use of digital technologies. Prior studies have predominantly examined road safety from fragmented perspectives, often positioning technology as a supporting factor rather than a systemic component. Consequently, empirical evidence on the mediating role of technology in strengthening road safety policy outcomes remains limited, particularly within developing country contexts. This study addresses this gap by conceptualizing technology as a mediating variable within the national road safety policy framework. A quantitative approach was adopted using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method, based on survey data from 1,000 respondents comprising policymakers, law enforcement officers, transportation stakeholders, and road users. The findings demonstrate that the five road safety pillars, safe systems, safe roads, safe vehicles, safe road users, and post-crash management have a positive and statistically significant effect on road transportation safety performance. In addition, technology was empirically validated as a significant mediating variable that enhances the effectiveness of each safety pillar. These results emphasize the strategic importance of digital transformation for achieving integrated, evidence-based road safety governance. Policy implications include strengthening integrated data systems, reinforcing lead agency functions, enhancing institutional capacity, and adopting a Digital Safe System approach.